Change in strong Eastern Pacific El Niño events dynamics in the warming climate - Carréric, Aude (2020)
While there is evidence that ENSO activity will increase in association with the increased vertical stratification due to global warming, the underlying mechanisms remain unclear. Here we investigate this issue using the simulations of the NCAR Community Earth System Model Large Ensemble (CESM-LE) Project focusing on strong El Niño events of the Eastern Pacific (EP) that can be associated to flooding in Northern and Central Peru. It is shown that, in the warmer climate, the duration of strong EP El Niño events peaking in boreal winter is extended by two months, which results in significantly more events peaking in February–March–April (FMA), the season when the climatological Inter-Tropical Convergence Zone is at its southernmost location. This larger persistence of strong EP events is interpreted as resulting from both a stronger recharge process and a more effective thermocline feedback in the eastern equatorial Pacific due to increased mean vertical stratification. A heat budget analysis reveals in particular that the reduction in seasonal upwelling rate is compensated by the increase in anomalous vertical temperature gradient within the surface layer, yielding an overall increase in the effectiveness of the thermocline feedback. In CESM-LE, the appearance of strong EP El Niño events peaking in FMA accounts for one-quarter of the increase in frequency of occurrence of ENSO-induced extreme precipitation events, while one-third results from weak-to-moderate El Niño events that triggers extreme precipitation events because of the warmer mean SST becoming closer to the convective threshold. In CESM-LE, both the increase in mean EP SST and the change in ENSO processes thus contribute to the increase in extreme precipitation events in the warmer climate.